Education About Balanced Nutrition For Pregnant Women In Preventing KEK Lueng Baro village. Kecamatan Suka Makmue, Kabupaten. Nagan Raya - Kasmawati; Farisni, Teungku Nih (Jurnal EduHealth, 2022)
Nutrition is a substance obtained from staple foods that is very necessary in the process of growth as well as body health. Balanced nutrition and nutrition during pregnancy is a very important thing that must be fulfilled during pregnancy, because it greatly impacts the health of the mother as well as the growth and development of the baby during pregnancy and at birth. Communities, especially in Indonesia, nutritional problems in pregnant women are still often found. The cause of deficiency for pregnant women is chronic energy. The purpose of this study was to determine the difference in age with an understanding of the incidence of cake that is experienced by pregnant women located in the village of Leung Baro. Quantitative descriptive research that describes the description of the location. By using observation techniques (observation) to research sites, education and direct interviews with pregnant women in the village of Lueng Baro, Suka Makmue District, Nagan Raya Regency. Based on the results of the Paired Samples Test, it shows that the t value is -5.445 with a significance value of p = 0.000. From these results it can be seen that the significant value is <0.05. From the results obtained it can be stated that there is a significant difference in knowledge about preventing the occurrence of CED in pregnant women after being given education (p <0.05), the difference in knowledge can be seen from the pre-test value of 20.0% and after education the mother's knowledge increases with a value post-test reached 73.3%. Provision of Balanced Nutrition Education in the Prevention and Management of KEK in Pregnant Women, there is a change in the knowledge of pregnant women in Leung Baro Village, Suka Makmue District, Nagan Raya Regency